Change in the impression of rooms with interior wood finishes arranged differently: Questionnaire survey with the use of photographs for the analysis of impressions of rooms concerning living activities - Sakuragawa, S.(Shizuoka-ken. Industrial Research Inst. (Japan)) (Journal of wood science, 2006)
Efforts were made to quantify the impact of visual stimulation from interior wood finishes on the impression of room interiors, using feelings about living activities as indicators. Four types of room interiors with interior wood finishes used in different proportions were simulated. The room interiors were photographed from the same viewpoint. A survey was conducted by interviewing 200 test subjects. As a result of the analysis of principal components, it was found that desires of living activities obtained from the four photographs consisted of two factors: desires for calmness and desires for activities. A great desire for calmness was obtained from photographs showing wood materials. A weak desire for calmness and a strong desire for activities were obtained from a photograph that showed no wood materials. Great desires for both calmness and activities were obtained from a photograph showing wood materials used only as flooring material. As for an evaluation of “living,” the photograph of a room interior without wooden materials was evaluated as a place that test subjects did not feel like living in. The photograph showing wood materials used only as flooring material was evaluated as the place that test subjects most felt like living in, and considered most suitable as a living space.